BIO-FABRICATION OF A PRE-VASCULARIZED SKIN GRAFT USING A CO-AXIAL ELECTROSPINNING TECHNIQUE AND ENDOTHELIAL PROGENITOR CELLS - Shahinur Rahman; Shakib Ahmed; Zahidul Islam (Journal of Biomedical and Techno Nanomaterials, 2025)
Severe skin injuries caused by burns, chronic wounds, and trauma remain a major clinical challenge due to limited graft survival and delayed vascular integration following transplantation. Insufficient early vascularization frequently leads to ischemia and graft failure, restricting the effectiveness of conventional tissue-engineered skin substitutes. This study aims to develop a pre-vascularized skin graft using a co-axial electrospinning technique integrated with endothelial progenitor cells to enhance early vascular functionality and graft viability. An experimental biofabrication approach was employed, involving the fabrication of core–shell electrospun fibrous scaffolds, encapsulation of endothelial progenitor cells, and comprehensive structural and biological evaluation in vitro. Scaffold morphology, porosity, and integrity were characterized, followed by assessment of cell viability, proliferation, endothelial marker expression, and formation of vascular-like networks. The results demonstrated that co-axial electrospinning produced uniform, highly porous fibrous scaffolds capable of maintaining endothelial progenitor cell viability and supporting their angiogenic behavior. Encapsulated cells exhibited sustained proliferation and organized into capillary-like structures within the scaffold matrix, while scaffold architecture remained structurally stable. These findings indicate that the proposed biofabrication strategy enables intrinsic pre-vascularization of engineered skin grafts prior to implantation. In conclusion, co-axial electrospinning combined with endothelial progenitor cells represents a promising and scalable approach for generating pre-vascularized skin grafts, with significant potential to improve graft integration and clinical outcomes in regenerative skin therapy.